PEMBUATAN SEDIAAN KOMBINASI SERBUK DARI BIJI PEPAYA (Carica papaya L) DAN SELEDRI (Apium graviolens L) UNTUK MEMELIHARA KESEHATAN RAMBUT - Nurlita Ekawati Putri; Agus Djamaludin; Dewi Ratnasari (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2022)
Background: Hair is something that grows from the dermis layer and through the ducts of hair follicles out of the skin. Hair loss is an event where hair is removed from the head abnormally, generally losing 80-120 strands / day. Many plants can be used to treat hair health, one of which is by using papaya seeds. Papaya seeds contain the coloring substances glucoside cacarindan and karpain which can discolor hair. One of the plants that can be used to nourish hair is celery. Celery leaves are known to have vasodilator activity that can stimulate hair growth. The purpose: Make powder preparations from papaya seeds and celery to treat hair health and organoleptic stability powder preparations from papaya seeds and celery Method: The research method used is action research. The preparation is made by mixing 7 grams of papaya seeds and 5 grams of celery leaves that have been previously dried first and then finely ground, and packaged with aluminum foil.. Results: Shows the results of powder preparations from papaya seeds and celery that are stable and durable for 3 weeks. Conclusion: The powder was stored in storage for 3 weeks at room temperature and a stable cold temperature for 3 weeks.